IMPROVING LEARNING THROUGH SCAFFOLDING - Rashidova, Munavvar Xaydarovna; Namozova , Dilnoza Berdimurotovna (Educational Research in Universal Sciences, 2023)
One of the main benefits of scaffolded instruction is that it provides for a supportive learning environment. In a scaffolded learning environment, students are free to ask questions, provide feedback and support their peers in learning new material.